Herbaceous plant species invading natural areas tend to have stronger adaptive root foraging than other naturalized species - Keser, Lidewij H.; Visser, Eric J. W.; Dawson, Wayne; Song, Yao-Bin; Yu, Fei-Hai; Fischer, Markus; Dong, Ming; van Kleunen, Mark (Frontiers in Plant Science, 2015)
Although plastic root-foraging responses are thought to be adaptive, as they may optimize nutrient capture of plants, this has rarely been tested. We investigated whether nutrient-foraging responses are adaptive, and whether they pre-adapt alien species to become natural-area invaders. We grew 12 pairs of congeneric species (i.e. 24 species) native to Europe in heterogeneous and homogeneous nutrient environments, and compared their foraging responses and performance. One species in each pair is a USA natural-area invader, and the other one is not. Within species, individuals with strong foraging responses, measured as root diameter and specific root length, had a higher biomass. Among species, the ones with strong foraging responses, measured as root length and root biomass, had a higher biomass. Our results therefore suggest that root foraging is an adaptive trait. Invasive species showed significantly stronger root-foraging responses than non-invasive species when measured as root diameter. Biomass accumulation was decreased in the heterogeneous versus the homogeneous environment. In aboveground, but not belowground and total biomass, this decrease was smaller in invasive than in non-invasive species. Our results show that strong plastic root-foraging responses are adaptive, and suggest that it might aid in pre-adapting species to becoming natural-area invaders.